Biological aging accelerates hepatic fibrosis: Insights from the NHANES 2017–2020 and genome-wide association study analysis - Jiaxin Zhao; Huiying Zhou; Rui Wu; Chen Ruan; Cheng Wang; Jiawei Ding; Tao Zhang; Zheyu Fang; Huilin Zheng; Lei Zhang; Jie Zhou; Zhenhua Hu (Annals of Hepatology)
Introduction and Objectives: This study aimed to investigate the association between biological aging and liver fibrosis in patients with metabolic dysfunction-associated steatotic liver disease (MASLD). Materials and Methods: We analyzed NHANES 2017–2020 data to calculate phenotypic age. Hepatic steatosis and fibrosis were identified using controlled attenuation parameters (CAP), fatty liver index (FLI) and transient elastography (TE). The odds ratios (ORs) and 95 % confidence intervals (CI) for significant MASLD fibrosis were calculated using multivariate logistic regression, and subgroup analyses were performed. We explored the potential causal relationship between telomere length and liver fibrosis using Mendelian randomization (MR). Additionally, we used the expression quantitative trait loci (eQTL) method and GSE197112 data to identify genes related to liver fibrosis and senescence. Finally, the APOLD1 expression was validated using GSE89632. Results: Phenotypic age was associated with liver fibrosis occurrence in MASLD (OR = 1.08, 95 % CI 1.05–1.12). Subgroup analyses by BMI and age revealed differences. For obese or young to middle-aged MASLD patients, phenotypic age is significantly associated with liver fibrosis. (OR = 1.14, 95 % CI 1.10–1.18; OR = 1.07, 95 % CI 1.01–1.14 and OR = 1.14, 95 % CI 1.07–1.22). MR revealed a negative association between telomere length and liver fibrosis (IVW method: OR = 0.63288, 95 % CI 0.42498–0.94249). The gene APOLD1 was identified as a potential target through the intersection of the GEO dataset and eQTL genes. Conclusions: This study emphasized the link between biological aging and fibrosis in young to middle-aged obese MASLD patients. We introduced phenotypic age as a clinical indicator and identified APOLD1 as a potential therapeutic target.